Penatalaksanaan Fisioterapi pada Kasus Kompresi Fraktur Thorakal 12 – Lumbal 1 Stadium Post Imobilisasi di Rumah Sakit Efarina Brastagi - Muliati, Muliati; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Haris, Muhamad (Jurnal Riset Hesti Medan, 2025)
Indonesia is one of the countries with a relatively high rate of traffic accidents. Data from the Indonesian National Police in 2009 indicates that at least 57,726 traffic accidents occurred on public roads that year. This means that an accident occurred once every 9.1 minutes (Ministry of Transportation, 2010). The consequences for the victims themselves can include both physical and psychological effects. A patient named Mrs. Suhaeriah, aged 57, was diagnosed with a lumbar compression fracture at L1-T12. The physiotherapy issues identified included complaints of pain, muscle spasms, reduced range of motion, decreased functional activity in the lower back, and the patient also reported difficulty bending over, standing for long periods, walking long distances, and performing household chores. Transcutaneous electrical nerve stimulation (TENS) is one of the interventions performed by physical therapists, utilizing low-voltage electrical currents to reduce pain in patients with lumbar compression fractures at T12 and L1. TENS can be used for acute pain with high frequency, high pulse width, and amplitude adjusted to the patient’s subjective comfort and perceived sensation. Core stability exercises are exercises that facilitate continuous isometric contraction of the deep spinal muscles at the lower levels, integrating into progressive functional training. Core stability exercises utilize motor learning principles to facilitate coordination of the deep spinal muscles.